New Approaches to Building Pathology and Durability - Delgado, João M.P.Q (Building Pathology and Rehabilitation,, 2016)
This book presents a collection of recent research works intended to assist in the effective management of service loss. It develops and evaluates methodologies for the assessment of defects and failures, and proposes methodologies for preventing and mitigating building defects. As such, the book will appeal to a broad readership of scientists, practitioners, students and lecturers.